Growth parameters of the clupeids Limnothrissa miodon and Stolothrissa tanganicae in northern Lake Tanganyika (Bujumbura sub-basin) - Mulimbwa, N´Sibula T.; Gordó-Vilaseca, Cesc; Milec, Leona J. M.; Patel, Deepti M.; Kankonda, Busanga Alidor; Micha, Jean-Claude; Sarvala, Jouko; Raeymaekers, Joos A. M. (Royal Belgian Institute of Natural Sciences, 2025)
The analysis of growth parameters in fish stocks, such as the asymptotic length (L∞) and the curvature parameter (K), is crucial for the estimation of production rates and total mortality rates in fisheries management. Here, we estimated the growth parameters of the clupeids Limnothrissa miodon and Stolothrissa tanganicae in the northern part of Lake Tanganyika (Bujumbura sub-basin). Both species are important targets of pelagic fisheries, but the available estimates are based on scarce size frequency data, and rarely on size as a function of age data. We provide new estimates of L∞ and K based on size as a function of age data, with age being inferred from otolith weights. Furthermore, we reanalyze several existing length frequency datasets using advanced statistical procedures to test if growth parameters estimated by length frequency analysis are consistent with those obtained from size as a function of age. We found that length frequency analysis consistently underestimates L∞ and overestimates K as compared to length-at-age data. We recommend that length-at-age data are collected at a much broader spatial and temporal scale than currently available to advance our understanding of the growth dynamics of these two sardine species. This will improve the assessment of stock productivity of Lake Tanganyika’s pelagic fisheries and the conservation of these economically important fish species.